Development of multi-axis numerical control program for mill—turn machine - She, Chen-Hua; Hung, Chih-Wei (Proceedings of the Institution of Mechanical Engineers. Part B, Journal of engineering manufacture, 2008)
A mill—turn machine combining a lathe and machining centre can perform turning and milling operations on the same machine. It can machine a workpiece in one set-up and eliminate errors that can be produced by moving the workpiece between turning and milling machines. Since the mill—turn machine has a complex configuration in which linear and rotary movements are non-orthogonal, generating the part program manually is almost impossible. This work develops an interface called a postprocessor that converts cutter location data generated by a general commercial computer-aided design (CAD)/computer-aided manufacturing (CAM) system into the numerical control (NC) data dedicated for the mill—turn machine. The form-shaping function matrix of the mill—turn machine, which describes the motion trajectory of tool points relative to the workpiece, is derived by the homogeneous coordinate transformation matrix. The complete analytical equations for NC data are obtained through a form-shaping function matrix and inverse kinematics. A window-based postprocessor system written in Borland C++ Builder and OpenGL was developed according to the proposed algorithm. Solid cutting simulation software is utilized to verify the effectiveness of the proposed algorithm.